2013
DOI: 10.1161/circulationaha.113.002434
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Lung p53 by Nutlin-3a Prevents and Reverses Experimental Pulmonary Hypertension

Abstract: Background— Induction of cellular senescence through activation of the p53 tumor suppressor protein is a new option for treating proliferative disorders. Nutlins prevent the ubiquitin ligase MDM2 (murine double minute 2), a negative p53 regulator, from interacting with p53. We hypothesized that cell senescence induced by Nutlin-3a exerted therapeutic effects in pulmonary hypertension (PH) by limiting the proliferation of pulmonary artery smooth muscle cells (PA-SMCs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 37 publications
7
94
1
1
Order By: Relevance
“…More importantly, considerable evidence indicated that the thickened medial layer of HPH regressed most obviously during reoxygenation 41. The present study showed that the reversal of thickened medial layer played a crucial role in the reversal of hypoxic pulmonary arterial remodeling.…”
Section: Discussionsupporting
confidence: 58%
“…More importantly, considerable evidence indicated that the thickened medial layer of HPH regressed most obviously during reoxygenation 41. The present study showed that the reversal of thickened medial layer played a crucial role in the reversal of hypoxic pulmonary arterial remodeling.…”
Section: Discussionsupporting
confidence: 58%
“…46 Thus, TCTP is a promising candidate factor in the "pseudomalignant" changes in vascular cell phenotype that have recently been described in PAH. TCTP (histamine-releasing factor) 29 is also a potent mediator of chronic inflammation and has been implicated in the lack of resolution of airway inflammation in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia induces proliferation of vascular smooth muscle cells, probably mediated by downregulation of CDKN1A 23 . In another study, this pro-proliferative and anti-senescent effect was enhanced in animals lacking CDKN1A 4 . Since miRNAs are an emerging group of factors that regulate gene expression, we performed an in silico approach to identify miRNAs that potentially target CDKN1A.…”
Section: Discussionmentioning
confidence: 86%
“…The contradictory results in our and previous studies are not fully explained at this moment, but might, similar to the paradoxical vasoconstriction induced by hypoxia, represent a unique feature of pulmonary vessels. Since the p53 activator Nutlin-3a required the presence of CDKN1A to improve hemodynamics and prevention of remodeling in hypoxia-induced PH 4 , we suggest that CDKN1A, rather than p53, is the critical factor that regulates proliferation of vascular smooth muscle cells in the development of pulmonary vascular remodeling.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation